A transznacionalizmustól a globalizációig : a közép-kelet-európai kisnépek dilemmái a történelmi tanulságok alapján - Bertalan, Péter; Pintér, Attila (Közép-Európai Közlemények, 2008)
Hungary is searching for its place not only within the European Union but also within a globalising world as well as within its smaller region, in Central- and Eastern Europe. It is not easy to find the right direction under complicated international circumstances. The press is keeping a close eye on our foreign political steps. OMV’s the Austrian oil and gas company’s struggle for MOL plays an important part in this. Hungary’s energy supply could be improved by buying natural gas through gas pipelines starting from one of Croatia’s Adriatic ports from the gas transported by liquefied natural gas tankers. This would make Hungary partly independent from Russian transports. In addition, developing traffic infrastructure could also tighten our economic relationships with Croatia, and indirectly with the whole Mediterranean region.